REWARD BASED CROWDFUNDING SEBAGAI SKEMA PENDANAAN WIRAUSAHA SOSIAL: TANTANGAN DAN PELUANG MENCAPAI INKLUSIVITAS EKONOMI DI INDONESIA - Wafi, Mochamad Adli; Zelsadila, Ajoenda; Nariswari, Alyca Azka (IBLAM LAW REVIEW, 2023)
The development of financial technology (fintech) has brought many benefits to the entrepreneurial world. However, access to fintech is not friendly to social entrepreneurs. In this respect, the growth of social entrepreneurship in Indonesia has challenges related to financing. Based on these problems, the author tries to find a solution. The acquisition of this research data is based on the results of regulations of laws or other written legal sources using methods of normative jurisprudence research. The author also uses a conceptual approach by deepening the theories in related discussions.Subsequently, the results of this research were compiled using qualitative descriptive methods, namely analysis to classify, compare, and link the obstacles to the development of social entrepreneurship in Indonesia with financial technology as a source of funding. Based on the method, the author found that the main challenge of social enterprise lies on the side of financing, and the survey results showed that crowdfunding, which is reward-based, became a medium to accommodate the needs of social businessmen so that inclusive economic justice can be achieved in Indonesia.